The brain-specific neural zinc finger transcription factor 2b (NZF-2b/7ZFMyt1) suppresses cocaine self-administration in rats - Chandrasekar, Vijay; DREYER, Jean-Luc (Frontiers in Behavioral Neuroscience, 2010)
Brain-specific neural-zinc-finger transcription factor-2b (NZF2b/7ZFMyt1) is induced in the mesolimbic dopaminergic region after chronic cocaine exposure and lentiviral-mediated expression of NZF2b/7ZFMyt1 in the nucleus accumbens results in decreased locomotor activity (Chandrasekar and Dreyer, 2009). In this study the role of NZF2b/7ZFMyt1 in active cocaine seeking and of its interaction with histone deacetylase on the altered behavior has been observed. Localized expression of NZF2b/7ZFMyt1 in the nucleus accumbens resulted in attenuated cocaine self-administration, whereas silencing this transcription factor with lentiviruses expressing siRNAs increased the animal′s motivation to self-infuse cocaine. Low doses of sodium butyrate, a potent inhibitor of histone deacetylase, were sufficient to reverse the NZF2b/7ZFMyt1-mediated decrease in cocaine self-administration. NZF2b/7ZFMyt1 expression resulted in strong induction of transcription factors REST1 and NAC1 and of the dopamine D2 receptor, with concomitant inhibition of BDNF and its receptor TrkB. We show that NZF2b/7ZFMyt1 colocalizes with histone deacetylase-2 (HDAC2), probably overcoming the suppression of transcriptional activity caused by Lingo1. These findings show that molecular adaptations mediated by NZF2b/7ZFMyt1 expression possibly lead to decreased responsiveness to the reinforcing properties of cocaine and play a prominent role in affecting the behavioral changes induced by the drug.